The Pragmatic Analysis of Deixis in Hotel Transylvania Movie Script 2012 - Muhamad Rizky Fathurrahman Subekti; Endang Fauziati (JELITA, 2025)
This study examines the pragmatic analysis of deixis in the script of the 2012 animated film Hotel Transylvania. The study utilises a qualitative descriptive research approach to define the type of deixis, elucidate their function of deixis, and analyze their pragmatic role, encompassing personal, spatial, temporal, discourse, and societal deixis, as manifested in the film's conversation. Employing Yule’s (1996) and Levinson’s (1983) frameworks, the results indicate that personal deixis predominates the script, delineating relationships and emotional profundity, especially between Dracula and his daughter, Mavis. Spatial deixis differentiates the monster hotel as a secure refuge from the human realm, hence reinforcing theme dichotomies. Temporal deixis organises the narrative chronology, generating suspense and emphasising generational disparities. Discourse deixis preserves cohesiveness and amplifies humour, whereas social deixis highlights hierarchy and closeness in character interactions. The study emphasises that deixis not only aids communication but also enriches storytelling by connecting linguistic expressions to wider narrative and emotional contexts. This research enhances pragmatic studies by providing insights on deixis in animated films, specifically in interactions between human and supernatural characters, thereby deepening the comprehension of language use in varied narrative contexts.